A Harnack Inequality Approach to the Interior Regularity Gradient Estimates of Geometric Equations (Journal of Partial Differential Equations, 2006)
In this paper we prove the gradient estimates for fully nonlinear geometric equation using a normal perturbation techniques.
Keywords: Fully nonlinear equation; geometric equation; gradient estimate